I love being me! - Roe, Mechal Renee (New York Random House, 2020)
Illustrations and rhyming text reveal all of the things girls love about themselves, from their nose, toes, and skin to their ability to spin, run, and cook
English Stories
Ages 3-5
Keywords: Self-esteem -- Fiction; Stories in rhyme; Picture books; Readers (Publications)